Sistema de monitoreo y control de temperatura para el patrón nacional de viscosidad - Blancas, J.; Conejo, A. (Revista Mexicana de Ingenieria Biomedica, 2000)
We have developed a monitoring and control system for the temperature of the water bath in which required a temperature of 293.150 K +/- 5 mK, this uncertainty is necessary so that it can work like the national patron. Inside of this bath will introduce the master's capillaries viscosimeters that will use like a reference for the calibration of the viscosimeters that will arrive at National Center of Metrology. The control of temperature is made by an electrical resistor of 1500 W. This resistor’s heat is made electrically by using the wide of pulse technique (PWM).